Vision-based egg grade classifier - Zalhan M.Z.; Sera Syarmila S.; Mohd Nazri I.; Mohd Taha I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Coordinate measuring machines; Human computer interaction; Image classification; Image enhancement; Intelligent systems; Medical imaging; Military photography; Classification algorithm; Digital image processing technique; Human computer interfaces; Image filtering; Image processing technique; Industrial inspections; Object classification; Vision systems; Image processing